Weird Tales, Volume 1, Number 2, April, 1923: The unique magazine - Various; Baird, Edwin, 1886-1957 (Salt Lake City, UT : Project Gutenberg, 2022)
"Weird Tales, Volume 1, Number 2, April 1923" is a collection of short stories edited by Edwin Baird, published in the early 20th century. This magazine is a showcase of speculative fiction, featuring a range of thrilling and imaginative tales that delve into the weird and the supernatural. The issue presents stories covering various themes from horror and fantasy to crime and adventure, with contributors like Carl Ramus, Paul Suter, and Roylston Markham. The opening portion of this volume highlights the contents of the magazine and begins to narrate "The Scar," a novelette by Carl Ramus. In this story, two doctors, Dr. Herbert Carlson and Dr. Clark Edwards, discuss recent crimes, including a notable kidnapping case. As the tale unfolds, Carlson receives an urgent call to attend to a very sick patient but is soon thrown into a dangerous situation involving masked captors. The tension escalates as Carlson must navigate both his medical expertise and the threat posed by his captors, setting the stage for a gripping and suspenseful narrative. (This is an automatically generated summary.)
Release date is 2022-12-22
Wouter Franssen and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Adventure stories -- Periodicals; Fantasy literature, American -- Periodicals; Fantasy literature, English -- Periodicals; Horror tales, American -- Periodicals; Horror tales, English -- Periodicals